Assessment Of Jordanian Nurses' Knowledge To Perform Glasgow Coma Scale - Hamza Al-Quraan; Mohannad Eid AbuRuz (European Scientific Journal, ESJ, 2016)
The most important assessment of neurological examination in the clinical setting is assessing level of consciousness. The first neurological tool used to assess patients' level of consciousness was the Glasgow Coma Scale. It is considered as the most common less subjective gold standard coma assessment tool. The purpose of this study was to assess Jordanian nurses' knowledge about Glasgow Coma Scale. A non-experimental, descriptive cross-sectional correlational design was performed in four (3 private hospitals and 1 governmental) hospitals in Amman-Jordan. A self-reported questionnaire was answered by all (ICU, CCU, ER, and Telemetry) nurses who accepted to participate in the study. A total of 200 questionnaires were distributed to the participants with 90% response rate ending with 180 questionnaires in the final analysis. More than half of the sample (56.7%) was males. The participants were young nurses with mean age of 26.3±8 years. The total mean score for the whole sample was 7.38 ± 1.96. There was no relationship between experience, level of education, and training course and knowledge level. Nurses working in accredited hospitals and governmental hospitals recorded more level of knowledge than other hospitals. Emergency Room nurses recorded less level of knowledge than other area of practice. In conclusion, knowledge about Glasgow Coma Scale is a global problem. Jordanian nurses, as other nurses, have inadequate knowledge to perform Glasgow Coma Scale assessment. It is vital and necessary to include educational programs about Glasgow Coma Scale for nurses in all areas of practice and in the curricula of nursing colleges.